Technology development in construction: a continuum from distant past into the future - Skibniewski, Mirosław J.; Zavadskas, Edmundas K. (Journal of Civil Engineering and Management, 2013)
This paper deals with the historical and current trends in the development of civil engineering and construction technologies. The authors demonstrate the continuity of creative thought and effort among early master builders and technology developers throughout the history of civilizations that created the most iconic structures remaining in the world heritage of the built environment to the contemporary times. Recent concepts and ongoing efforts in the development of advanced construction technologies based on automation and information sciences, materials science and systems engineering are highlighted in the context of historical ideas and achievements of past architects and construction engineers of the past century.